NEW APPROACHES TO IMPROVE AUTODERMAPLASTY RESULTS - Abdurakhmanov, F.M.; Khamdamov, Sh. A.; Korikhonov, D.A.; Okhunov, A.O.; Boboev, K.Kh.; Bobokulova, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Wound healing in diabetic foot syndrome is a serious problem in treating patients with diabetes mellitus. Purulent-necrotic diseases of the foot are the most common cause of disability and death in patients with diabetes mellitus. Amputation of the lower limb is most often caused by the occurrence of ischemic gangrene, neuropathic ulcers, and the progressive development of necrosis and infection. This is due to the atypical course of the wound process in diabetes mellitus. Material. The results of plastic surgery to eliminate wounds in patients with diabetic foot syndrome are analyzed. Morphological, cytological and planimetric research methods were used to evaluate the results. Conclusion. Features of the course of the wound process after dermaplasty in patients with diabetic foot syndrome are the wave-like course of inflammatory processes with a subsequent decrease in their intensity. The use of Azacytidine changes the course of the process of engraftment of the skin flap in diabetic foot syndrome, reducing the duration and intensity of inflammation.